PENGARUH MULSA DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN - nurhalizah loilainge; Hertasning Yatim; Wawan Setiawan (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2023)
Cucumber is one of the horticultural crops that is widely cultivated by farmers in our country, Indonesia. The purpose of this study was to determine the growth and yield of cucumber plants by applying plastic mulch and applying chicken manure. This research was carried out from June to September 2021 in Sisipan Village, Batui District, Banggai Regency. This study used a factorial randomized block design (RBD) consisting of 2 factors. Parameters observed in this study included plant height (7, 14, 21, and 28 DAP), number of leaves (7, 14, 21 and 28 DAP), fruit length (first and second harvests), fruit diameter (first and second harvests) and fruit weight (first and second harvest). The research data were analyzed using the F test of variance analysis and continued with the Honest Significant Difference Test (BNJ) at the 5% level. The results of the study had a significant effect on the plastic mulch treatment on plant height at 7 HST, 14 HST and 21 HST. Number of leaves at the age of 7 HST, 14 HST, 21 HST and 28 HST. The length of the first harvest fruit. The diameter of the fruit of the first harvest and the second harvest. The weight of the first harvest fruit. The application of chicken manure had a significant effect on the length of the first harvest fruit and the weight of the first harvest fruit on cucumber plants.